FLUSHING SYSTEM FOR CERAMIC SANITARY WARE - MANAV, Sefa; KEMANECI, Halil Ibrahim; SIMSIR, Bogac (2023)
The subject of the invention relates to a flushing system, which is developed for providing the hygiene of the ceramic sanitary ware and which enables the flushing fluids to be guided into the bowl of the ceramic sanitary ware. The flushing system (4) developed within the scope of the invention comprises at least one distributor piece (41), at least one rosette (43) for the inflow of the cleaning fluid or the clean water to the ceramic sanitary ware bowl (33) and at least one transmission channel (42), which provides the connection between the distributor piece (41) and the rosette (43) and which is fixed at one end thereof to the distributor piece (41) and at the other end thereof to the rosette (43). L'objet de l'invention concerne un système de rinçage, qui est développé pour assurer l'hygiène de l'article sanitaire en céramique et qui permet aux fluides de rinçage d'être guidés dans la cuvette de l'article sanitaire en céramique. Le système de rinçage (4) développé dans le cadre de l'invention comprend au moins une pièce de distribution (41), au moins une rosette (43) pour l'entrée du fluide de nettoyage ou de l'eau propre dans la cuvette de l'article sanitaire en céramique (33) et au moins un canal de transmission (42), qui assure la liaison entre la pièce de distribution (41) et la rosette (43) et qui est fixé à une extrémité correspondante à la pièce de distribution (41) et à l'autre extrémité correspondante à la rosette (43).